PRINSIP-PRINSIP HUKUM TENTANG TINDAK PIDANA PENGHINAAN DAN PENCEMARAN NAMA BAIK DALAM PERPSPEKTIF PERLINDUNGAN HAK ASASI MANUSIA - Nanda Yoga Rohmana (Yuridika, 2017)
International Convention on both the UDHR and ICCPR which guarantee the right of freedom of speech and protection of one's honor and good name. While the Constitution has also guaranteed by Article 28E, 28F and 28G. In the rate level the Act still contained their conflict of law rules among specific law, but it also contained vagueness of the rule of law contained in Article 27 paragraph 3 of the Act ITE and Articles 310 and 311 of the Criminal Code that do not reflect the lex certa and lex scripta. Although there have been special criminal eraser reasons contained in Article 310 paragraph 3 Penal Code in the form of a defense of necessity and in the public interest, but in theory difficult to apply because of lack of the concept of the special criminal eraser reasons. In addition, there is a void laws that have not been regulated in the Indonesian national law as a reason for a special criminal eraser. Legal issues discussed are ) The offenses insult and defamation in terms of the principles and laws of human rights, 2 Formulation of law and/or construction law related criminal offenses insult and defamation in order to balance the protection of freedom of speech and respect the individual's good name.